2006
DOI: 10.2169/internalmedicine.45.1515
|View full text |Cite
|
Sign up to set email alerts
|

A Fiveyear Comparison of the Renal Protective Effects of Angiotensin Converting Enzyme Inhibitors and Angiotensin Receptor Blockers in Patients with NonDiabeticNephropathy

Abstract: Objective Evidence suggests that the effectiveness of angiotensin-converting enzyme (ACE) inhibition diminishes with time, resulting in increasing angiotensin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…13 Angiotensin receptor blockers prevent acute renal failure and delay the process of chronic kidney disease. 13,32 Our previous studies showed that serum and urinary ACE activities were increased 24 h-48 h after contrast media administration. 14 The renal Ang II levels in contrast media groups were higher than control groups and telmisartan protected renal tissue from nephrotoxicity induced by contrast media in glycerin-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…13 Angiotensin receptor blockers prevent acute renal failure and delay the process of chronic kidney disease. 13,32 Our previous studies showed that serum and urinary ACE activities were increased 24 h-48 h after contrast media administration. 14 The renal Ang II levels in contrast media groups were higher than control groups and telmisartan protected renal tissue from nephrotoxicity induced by contrast media in glycerin-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of whether ARBs and ACE inhibitors are similarly effective in CKD that is not caused by diabetic nephropathy remains controversial (72,73).…”
Section: Prevention Treatment and Follow Upmentioning
confidence: 99%
“…Head-to-head comparisons of the 2 classes of drugs are scanty [15,16]. Barnett et al [15] made a double-blind trial on 250 subjects with type 2 diabetes and early nephropathy who were randomly assigned to receive either telmisartan or enalapril.…”
Section: Do Ace Inhibitors and Arbs Equally And Fully Suppress The Ras?mentioning
confidence: 99%
“…However, these findings do not necessarily apply to patients with more advanced nephropathy or non-diabetic CKD. Shoda et al [16] studied 68 non-diabetic patients with CKD and proteinuria, showing again no difference among the 2 classes of drugs. Unfortunately, the value of these findings is limited by the fact that study treatment was quite heterogeneous in the 2 groups.…”
Section: Do Ace Inhibitors and Arbs Equally And Fully Suppress The Ras?mentioning
confidence: 99%